2022
DOI: 10.1167/iovs.63.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporter 1 (MCT1) Mediates Succinate Export in the Retina

Abstract: Purpose Succinate is exported by the retina and imported by eyecup tissue. The transporters mediating this process have not yet been identified. Recent studies showed that monocarboxylate transporter 1 (MCT1) can transport succinate across plasma membranes in cardiac and skeletal muscle. Retina and retinal pigment epithelium (RPE) both express multiple MCT isoforms including MCT1. We tested the hypothesis that MCTs facilitate retinal succinate export and RPE succinate import. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…This transport is proton linked and is driven by changes in proton concentration (Halestrap & Price, 1999). Moreover, previous studies of muscle, heart, and recombinant protein have shown that MCT1 can transport succinate in its monocarboxylate form (Andrienko et al, 2017; Bisbach et al, 2022; Prag et al, 2021; Reddy et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This transport is proton linked and is driven by changes in proton concentration (Halestrap & Price, 1999). Moreover, previous studies of muscle, heart, and recombinant protein have shown that MCT1 can transport succinate in its monocarboxylate form (Andrienko et al, 2017; Bisbach et al, 2022; Prag et al, 2021; Reddy et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Here we show that brown adipocyte uptake of succinate depends on the proportion of it in the monocarboxylic form, and relies substantially on MCT family proteins, in particular MCT1. It is noteworthy that a mechanism through which succinate is acquired by brown adipocytes appears to be an inversion of the succinate export mechanism recently discovered in a variety of cell types (Bisbach et al, 2022; Prag et al, 2021; Reddy et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistently, Female mice show more severe RPE damage and reduced retinal thickness under oxidative damage induced by sodium iodate 63, 64 . RPE mitochondria prefer to oxidize succinate from the retina to produce malate and fumarate for the retina 65-67 . However, succinate is lower in female RPE under both fed and fasted states.…”
Section: Discussionmentioning
confidence: 99%
“…The normal fuel preferences for this tissue are not known, but likely include lactate and succinate. Those metabolites are released by retina tissue explants and consumed by RPE-choroid explants (7,8,11,13,15,16). As we had done with glucose, we determined the contribution of alternate fuels to tissue metabolism in vivo, using jugular vein infusions of 13 C 3 -lactate (Fig.…”
Section: S1d)mentioning
confidence: 99%